Incompatible Foods and Neurodevelopmental Disorders in Children: A Review of the Evidence (International Journal of Ayurveda and Pharma Research, 2025)
Neurodevelopmental disorders such as Attention Deficit Hyperactive Disorder (ADHD), autism and anxiety are becoming more common in India, posing a significant economic and social burden on the country. Despite extensive research the exact causes of ADHD and autism remain unclear. Both conditions are multifactorial involving genetic, environmental and biological factors. Poor diet being a significant contributing factor for the increasing prevalence of neurodevelopmental disorders. Objective: Investigate the relationship between diet and neurodevelopmental disorders like ADHD and autism, and explore Ayurvedic principles in understanding this relationship. Data source extensive research on neurodevelopmental disorders, Ayurvedic texts, and modern scientific studies on diet's impact on brain development and function. Review methods comprehensive review of existing research on neurodevelopmental disorders, Ayurvedic principles, and diet's impact on brain health, considering modern food consumption patterns. Result: Poor diet is a significant contributing factor to neurodevelopmental disorders. Consuming preserved foods, high sugar, and unhealthy fats leads to inflammation, oxidative stress, and disruption of the gut-brain axis. Conclusion: Ayurvedic principles provide valuable insights into the relationship between diet and neurodevelopmental disorders. Identifying new food incompatibilities relevant to modern food consumption patterns may help develop dietary interventions to prevent or manage these disorders.